The Relationship Of Knowledge With Mother's Attitudes Pregnant About Gestational Diabetes Mellitus In Baru Village - Astuti, Tri Yuni; Simarmata, Mesrida; Syahputra , Indrawan (INTERNATIONAL JOURNAL OF MIDWIFERY RESEARCH, 2024)
Background : Diabetes Mellitus Gestational (GDM) is incident improvement glucose in the mother pregnant sick from disturbance tolerance in mother pregnant . can happened to the mother pregnant Because happen improvement estrogen and progesterone hormones so increase hyperplasia pancreatic beta cells so insulin release increases and experiences resistance at the beginning pregnancy . Disorders vision , preeclampsia , fetus large , miscarriage , prolonged labor , premature , cesarean delivery Method : Design study Which used in study This that is analytic correlation with approach cross-sectional . Time and place research : Research This held in June 2024 in New Village , Hinai District , The Land of the Rising Sun North Sumatra Province in 2024. Population and sample : population is Mother pregnant women in Desa Baru with a total sampling of 42 people. Result: Respondents majority knowledge Enough as much as 18 people (43%) and based on attitude majority positive as many as 33 people (79%). Chi square test results obtained is 0.002 . or (0.05). This is state There is connection between knowledge somebody with attitude against diabetes mellitus gestational . Conclusion : There is a relationship knowledge to attitude Mother pregnant about Diabetes Mellitus Gestational so need done improvement knowledge for mothers pregnant behave positive in prevention of diabetes mellitus Gestational